Intra-settlement politics and conflict in enumerations. (October 2017) - Rigon, Andrea
While traditionally an instrument of government power, enumerations are increasingly conducted by urban communities themselves to gain recognition and negotiate with city authorities. Most literature focuses on the productive relationship between communities and government enabled by enumerations, and how enumerations transfer power to communities. However, in highly unequal informal settlements, it is very important to understand who within the community gets such power. Through the ethnographic account of an enumeration promoted by a slum-upgrading project in Nairobi, this paper makes a contribution to the analysis of power in enumerations. The article reveals the strategies of local elites to shape the exercise in their favour. Often, local elites present themselves as representatives of the wider community and draw on this power and legitimacy to advance their specific claims. Therefore, rather than looking only at the relationship between state and community, analyses of enumeration processes should also pay more attention to the complexity of internal communities' dynamics and conflicting interests, and how these play out in the relationships with the state.